2020
DOI: 10.1101/2020.06.04.133611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural insight into outer membrane asymmetry maintenance of Gram-negative bacteria by the phospholipid transporter MlaFEDB

Abstract: The asymmetric phospholipid outer membrane (OM) of Gram-negative bacteria serves as the first line of defense against cytotoxic substances such as antibiotics. The Mla pathway is known to maintain the lipid asymmetry of the OM by transporting phospholipids between the inner and outer membranes. Six Mla proteins MlaFEDBCA are involved, with the ABC transporter MlaFEDB acts through a mechanism yet to be elucidated. Here we determine cryo-EM structures of MlaFEDB in apo, phospholipid-, ADP-or AMP-PNP-bound state … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…This movement narrows the cytoplasmic allocrit binding pocket significantly ( It should be emphasized that the structural studies reported here support an anteretrograde direction for lipid transport, as supported by our previous biochemical data in A. baumannii (19) as well as other studies in E. coli (11,19,20). Nonetheless, other assays point towards a retrograde directionality (18,21), and the current structures do not conclusively preclude this. Further structural analyses, in particular in complex with the periplasmic carrier MlaC, will be required to definitely resolve this controversy.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This movement narrows the cytoplasmic allocrit binding pocket significantly ( It should be emphasized that the structural studies reported here support an anteretrograde direction for lipid transport, as supported by our previous biochemical data in A. baumannii (19) as well as other studies in E. coli (11,19,20). Nonetheless, other assays point towards a retrograde directionality (18,21), and the current structures do not conclusively preclude this. Further structural analyses, in particular in complex with the periplasmic carrier MlaC, will be required to definitely resolve this controversy.…”
Section: Discussionmentioning
confidence: 63%
“…While this manuscript was under review, three independent groups released the structure of the Escherichia coli MlaBDEF complex (MlaBDEFec), in a range of nucleotide states and with various solubilization approaches (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the proposed manner of lipid binding to MlaFEDB differs significantly among all three pre-prints posted around the same time. Our structure and the other E. coli MlaFEDB structure described by Tang, et al describe lipid binding to the outward-open pocket of MlaE (Tang et al, 2020), while the Acinetobacter baumannii MlaFEDB described by Mann, et al describes lipid binding sites at the pore of MlaD as well as six additional lipidbinding sites in between the pore loops of each of the six MCE domains in the MlaD ring (Mann et al, 2020). Tang et al observed density assigned to a single phospholipid bound in the outward-open pocket of MlaFEDB, with the head group facing towards the core of the MlaE dimer and tails pointing towards the MlaD pore.…”
Section: Discussionmentioning
confidence: 79%
“…The upward-facing acyl chain of lipid 2 is sandwiched between two tyrosine residues (Tyr81 from each MlaE subunit), and these residues also contact one of the acyl chains of lipid 1. Mutations of Tyr81 to either a smaller (Ala) or a larger (Trp) hydrophobic residue had no effect on E. coli growth in the presence of SDS+EDTA ( Figure 4—figure supplement 3 ), although a Tyr81Glu mutation was recently reported to impair MlaFEDB function ( Tang, 2020 ) (see Discussion).…”
Section: Resultsmentioning
confidence: 90%
“…A role for MlaFEDB in phospholipid export is supported by recent cellular studies in Acinetobacter baumannii ( Kamischke et al, 2019 ), as well as in vitro experiments with E. coli proteins, showing directional lipid transfer from MlaD to MlaC ( Ercan et al, 2019 ; Hughes et al, 2019 ). On the other hand, prior studies indicated that the Mla system is an importer ( Malinverni and Silhavy, 2009 ; Chong et al, 2015 ; Powers and Trent, 2018 ; Yeow et al, 2018 ), and in vitro reconstitution and transport assays suggest that MlaFEDB may be bi-directional, with a preference for import (retrograde transport) ( Tang, 2020 ). Concurrently with our preprint, two other groups also reported structures of the MlaFEDB complex on BioRxiv ( Coudray, 2020 ; Mann, 2020 ; Tang, 2020 ), and these structures appear to be similar overall, although the PDB coordinates are not yet available to analyze.…”
Section: Discussionmentioning
confidence: 99%